STRUCTURE OF CL-CONTAINING SILICATE AND ALUMINOSILICATE GLASSES: A 35CL MAS-NMR STUDY - Sandland T.O.; Du L.S.; Stebbins J.F.; Webster J.D. (My University, 2004)
Chlorine-35 magic angle spinning (MAS) nuclear magnetic resonance (NMR) spectra were collected at 14.1 and 18.8 Tesla fields to determine the atomic scale structural environments of the chloride ions in anhydrous and hydrous silicate and aluminosilicate glasses containing 0.2 to 0.7 wt% Cl. NMR peaks are broad and featureless, but are much narrower than the total chemical shift range for the nuclide in inorganic chlorides. Peak widths are primarily due to quadrupole interactions and to a lesser extent to chemical shift distributions. Peak positions are quite different for the Na- and Ca-containing glasses, suggesting that most Cl− coordination environments contain network modifier cations. Comparison of peak positions and shapes for silicate and aluminosilicate glasses containing either Na or Ca suggests that there is no obvious contribution from Cl− bonded to Al, and relative quantitation of peak areas indicates that there is no systematic undercounting of 35Cl spins in the aluminous vs. the Al-free samples. In Ca-Na silicate glasses with varying Ca/(Ca + Na), the mixed-cation glasses have intermediate chemical shifts between those of the end members, implying that there is not a strong preference of either Ca2+ or of Na+ around Cl−. Hydrous Na-aluminosilicate glasses with H2O contents up to 5.9 wt% show a shift to higher frequency NMR signal with increasing H2O content, while the quadrupole coupling constant (CQ) remains constant at ∼3.3 MHz. However, the change in frequency is much smaller than that expected if H2O systematically replaced Na+ in the first-neighbor coordination shell around Cl−. A series of hydrous Ca-aluminosilicate glasses with H2O contents up to 5.5 wt% show no shift in NMR signal with increasing H2O content. The CQ remains constant at ∼4.4 MHz, again suggesting no direct interaction between Cl− and H2O in these samples.